How to Increase Share of Product-Related Services in Revenue? Strategy Towards Servitization - Marjanovic, Ugljesa; Lalic, Bojan; Majstorovic, Vidosav; Medic, Nenad; Prester, Jasna; Palcic, Iztok (Advances in Production Management Systems. Smart Manufacturing for Industry 4. 0, 2018)
The process of creating value by adding services to product offerings, or servitization, has flourished in recent years. Manufacturing companies increasingly produce and provide services along with or instead of their traditional physical products. The provision of product-related services in emerging economies has been neglected and can tremendously improve understanding of service growth, especially in the field of billing. The aim of this study is to examine is it worthwhile for the manufacturing companies in transition countries to offer product-related services and what strategy should they pursue to build service business model. Our analysis used the Croatian, Serbian and Slovenian dataset from the European Manufacturing Survey conducted in 2015. Empirical results revealed that in manufacturing companies in transition countries product-related services can significantly increase share of revenue. Results indicate that management in manufacturing companies should directly invoice software development and revamping, and indirectly installation, and design, as product-related service to maximize firm’s turnover and create a service business model.